The MEGaN project: I. Missing formation of massive nuclear clusters and tidal disruption events by star clusters - massive black hole interactions - Arca Sedda, Manuel; Capuzzo-Dolcetta, Roberto (Arxiv, 2017)
We investigated the evolution of a massive galactic nucleus hosting a super-massive black hole (SMBH) with mass $M_SMBH=10^8 M_\odot$ surrounded by a population of 42 heavy star clusters (GCs). Using direct $N$-body modelling, we show here that the assembly of an NSC through GCs orbital decay and merger is efficiently inhibited by the tidal forces exerted from the SMBH. The GCs mass loss induced by tidal forces causes a significant modification of their mass function, leading to a population of low-mass ($<10^4$) clusters. Nonetheless, the GCs debris accumulated around the SMBH give rise to well-defined kinematical and morphological properties, leading to the formation of a disk-like structure. Interestingly, the disk is similar to the one observed in the M31 galaxy nucleus, which has properties similar to our numerical model. The simulation produced a huge amount of data, which we used to investigate whether the GC debris deposited around the SMBH can enhance the rate of tidal disruption events (TDEs) in our galaxy inner density distribution. Our results suggest that the GCs disruption shapes the SMBH neighbourhoods leading to a TDE rate of $\sim 2 × 10^{-4} $yr$^{-1}$, a value slightly larger than what expected in previous theoretical modelling of galaxies with similar density profiles and central SMBHs. The simulation presented here is the first of its kind, representing a massive galactic nucleus and its star cluster population on scales $\sim 100$ pc.